Role of the mesolimbic dopamine system in relief learning - Mayer, Dana; Kahl, Evelyn; Uzuneser, Taygun; Fendt, Markus (Neuropsychopharmacology, 2018)
The relief from an aversive event is rewarding. Since organisms are able to learn which environmental cues can cease an aversive event, relief learning helps to better cope with future aversive events. Literature data suggest that relief learning is affected in various psychopathological conditions, such as anxiety disorders. Here, we investigated the role of the mesolimbic dopamine system in relief learning. Using a relief learning procedure in Sprague Dawley rats, we applied a combination of behavioral experiments with anatomical tracing, c-Fos immunohistochemistry, and local chemogenetic and pharmacological interventions to broadly characterize the role of the mesolimbic dopamine system. The present study shows that a specific part of the mesolimbic dopamine system, the projection from the posterior medial ventral tegmental area (pmVTA) to the nucleus accumbens shell (AcbSh), is activated by aversive electric stimuli. 6-OHDA lesions of the pmVTA blocked relief learning but fear learning and safety learning were not affected. Chemogenetic silencing of the pmVTA-AcbSh projection using the DREADD approach, as well as intra-AcbSh injections of the dopamine D2/3 receptor antagonist raclopride inhibited relief learning. Taken together, the present data demonstrate that the dopaminergic pmVTA-AcbSh projection is critical for relief learning but not for similar learning phenomena. This novel finding may have clinical implications since the processing of signals predicting relief and safety is often impaired in patients suffering from anxiety disorders. Furthermore, it may help to better understand psychological conditions like non-suicidal self-injury, which are associated with pain offset relief.
EVALuna2:211709